A comparative analysis of the influence of contraceptive use and fertility desire on the duration of second birth interval in four sub-Saharan African countries. - Afolabi, Rotimi Felix; Fagbamigbe, Adeniyi Francis; Palamuleni, Martin Enock (BMC Women's Health, 2021)
Background: Fertility decline characterised by inter-birth intervals remains rather slow or stall in many countries of sub-Saharan African (SSA). Non-adherence to optimal inter-birth intervals often occasioned by low prevalence of contraceptive use and high fertility desires often lead to poor maternal and child health outcomes. Additionally, information on the influence of contraception and fertility desire on interval between first and second births (SBI) is rarely available. This study therefore aimed to examine the influence of fertility desire and contraception on SBI among women in four SSA countries.Methods: We analysed cross-sectional data on women aged 15-49 years who participated in the recent Demographic and Health Surveys in DR Congo, Ethiopia, Nigeria and South Africa. Semi-parametric Cox proportional hazards regression was employed for the analysis at 5% significance level.Results: The median time to second birth was 34 months in DR Congo; 35 months, Nigeria; 42 months, Ethiopia; and 71 months, South Africa. About 70% of the women desired additional child(ren) and two-thirds have never used contraceptive in both Nigeria and DR Congo. The hazard of second birth was significantly lower among women who desired additional child(ren) compared to desired for no more child in DR Congo (aHR = 0.93; CI: 0.89-0.97), Ethiopia (aHR = 0.64; CI: 0.61-0.67) and South Africa (aHR = 0.51; CI: 0.47-0.55). Women who had never used contraceptive were 12%, 20% and 24% more likely to lengthen SBI than those who were current users in DR Congo, Nigeria and South Africa respectively. DR Congo and Nigerian women were about two times more likely to shorten SBI compared with their South African counterparts. Other significant determinants of SBI include ethnicity, rural residential, age and marital status at first birth, wealth and employment status.Conclusion: Findings showed differentials in the linkage between second birth interval and the desired fertility and contraception by country, demonstrating the importance of context. The contribution of these factors to second birth interval requires country context-specific attention if further decline in fertility and poor health outcomes associated with sub-optimal inter-birth interval is to be attained in SSA.